Inovasi Hijau: Model Pendampingan UMKM Bengkalis Menuju Bisnis Berkelanjutan - S, Suharyono (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service activity aims to improve the operational performance of Micro, Small, and Medium Enterprises (MSMEs) through mentoring on green innovation strategies and the adoption of environmentally friendly behavior. MSMEs, as drivers of the local economy, face challenges in operational efficiency, waste management, and a lack of awareness of environmental sustainability. The training was conducted on Saturday, July 19, 2025, at Hotel Berlian Bengkalis, involving 21 MSME participants from various business sectors. The methods used included interactive material delivery, group discussions, practical simulations, and the formulation of environmentally friendly action plans. The results of the activity showed an increase in participants’ understanding of green innovation concepts, energy efficiency, plastic waste reduction, and the use of eco-friendly packaging. Participants also demonstrated a strong commitment to adopting sustainable business practices in their daily operations. This activity proves that participatory-based education can serve as an effective means of fostering environmental awareness among MSMEs.